Módulo tangente do tendão calcanear de idosas submetidas a protocolo crônico de alongamento - Martins, Natália Santos da Fonseca (2018)
Aging alters the mechanical properties of tendons. Flexibility training is highly widespread as a common practice for the elderly population despite the lack of a consensus about its benefits. A methodology to estimate the Achilles tendon tangent modulus of young male subjects was recently described. The aims of this study is to calculate the tangent modulus of the Achilles tendon of elderly women undergoing chronic stretching training and determine the reliability of the protocol. Twenty-one elderly women were divided in control (n = 12) and stretching (SG) (n = 9) groups. SG performed static stretching exercises for triceps surae, 3 times a week for 11 weeks. The results did not indicate significant differences in the tangent modulus between pre and post intervention conditions (422.92 ± 240.74 to 341.20 ± 153.88 MPa), however, it pointed out potential responders to training, indicating the need of individual analysis considering the previous conditions and their specific characteristics. The Intraclass Correlation Coefficient (ICC), the Typical Error Measurement (TEM) indicated good reliability suggesting that the methodology can be reproduced (ICC: 0,7 a 0,99 e TEM: 0,39 a 22,4%).